Prospects for Citizenship - Andrew Mason; Momoh Banya; Chris Armstrong; Gerry Stoker; Graham Smith; David Owen; Clare Saunders; Derek McGhee; Anthony McGrew (Bloomsbury Academic, 2013)
This book offers an incisive analysis of the problems and pressures of citizenship in the twenty-first century, focussing in particular on the apparent decline of traditional forms of civic engagement, the emergence of new forms of participation and the relationship between citizenship and globalization.
English